An Insight into Investment and Deposit Products Offered by Islamic Banks in Malaysia - Ahmad, Zaki; Rahman, Md Mahfujur; Khan , Issa (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
The aim of this paper is to understand the practical application of investment and deposit products in comparison with the guidelines offered by the Islamic Financial Services Act (IFSA). Here, the products’ features and benefits of the banks’ deposit and investment products are highlighted. A performance analysis of both products is conducted among different banks in Malaysia, and their results are used to draw conclusions on the effects of IFSA on banks. The data was based on two banks in Malaysia: one was a fully-fledged Islamic bank, and the other was a subsidiary bank offering Islamic banking products. The information was obtained from the banks’ websites, annual reports, and Bank Negara Malaysia’s (BNM) website. The findings of the research are that the two banks analyzed all conform to the guidelines issued by IFSA. The volumes of investment products have significantly decreased after the introduction of IFSA compared to the volumes of deposit products. Bank Islam and CIMB Islamic both provide items that are suitable for use with an IFSA. Customers have a thorough understanding of the benefits of various types of deposits and investments.